Réponses

2013-11-08T12:55:06+01:00
Bonjour

A=5x-4+7x-8x+6
A =  4x +2

B=-4y+5-2y²+y-8y²-3y-11

B = -10y² -6y -6

2013-11-08T13:01:39+01:00











A = 5x - 4 + 7x - 8x + 6
A = 5x + (–4) + 7x + (–8) x + 6A = 5x + 7x + (–8) x + (–4) + 6
A = (5 + 7 + (–8)) × x +2 = 4x + 2
Pourquoi ne peux-tu pas réduire davantage?
Parce-que 4x est prioritaire (multiplication)............


B = -4y + 5 - 2y² + y - 8y² - 3y - 11

B = (–2) y² + (–8) y ² + (–4) y + 1y + (–3) y + 5 + (–11)
B = (–2 + (–8)) y² + ((–4) + 1 + (-3)) y + (–6)
B = (–10) y² + (–6) y + (–6) = –10y² – 6y – 6